Two stage formation of median nerve in North-East Indian cadavers - Roy Dutta Rajat; Thakuria Santona; Bora Debabani; Das Kanta Tarini (Wolters Kluwer Medknow Publications, 2017)
Background and aims: The median nerve is formed by the union of the medial and lateral roots from the medial [C8, Tl] and lateral cords [C5, 6, 7] of brachial plexus respectively. The nerve is formed in the axilla embracing the axillary artery. Lateral root of median nerve is a terminal branch of lateral cord and medial root of median is a terminal branch of medial cord. Variations in the formation of the median nerve are common and have been reported by various authors. The aim of this study is to observe the variations in the formation of median nerve that would help in clinical evaluation. Materials & Methods: The present study was conducted in the Department of Anatomy, Jorhat Medical College, Jorhat. Fifteen embalmed and formalin fixed cadavers were studied for variation of the median nerve. The dissections were carried out according to the Cunningham's Manual of practical Anatomy. In total 30 upper limb specimens were used for the study. Results: Out of 30 upper limbs, in three limbs [10%] there was duplication in the formation of the median nerve. Among the three, two specimens were of right side and one from the left side. Conclusion: We know that brachial plexus is located in axilla and axillary region is important not only from anatomical point of view but also from various clinical aspects as well. Awareness about the many variations of brachial plexus is important in understanding nerve blocks, diagnostic imaging, trauma and surgery